KAJIAN WARNA DAN UJI ORGANOLEPTIK PADA KLON UBI JALAR (Ipomea batatas L.) - Rita Hayati; Mardhiah Hayati (Jurnal Agrotek Lestari, 2018)
Study of color and organoleptic tests on sweet potato clones has been done. Indonesia is a country that has the potential availability of food as a source of carbohydrate that is large enough in terms of resource potential of the region, one of the sources of carbohydrates are types of tubers such as sweet potato (Ipomoea batatas L.). Diversification on sweet potatoes can be used as an alternative community in meeting the food other than rice. The potential and benefits of sweet potato as an alternative food material is enormous, especially in improving human nutrition and food security. The purpose of this study was to determine the color and panelists acceptance of the sweet potato clones. Result of this study was to obtain preliminary information about color and preference of the panelists on sweet potato clones before it is processed. The results showed that the color of sweet potatoes significantly different at all clones of sweet potato, sweet potato color of the brightest contained in sweet potato clones K15 followed K7 and K9. Panelists preferred the clones K6, while the form of panelists selecting clones K6, K2, followed by K11, K12, K13, K14 and K16. As for the exterior texture, panelists chose K16, and textures in the selected panelists is K1, K10 and K13. Keywords: clone, color, organoleptic, sweetpotato